2007
DOI: 10.1088/0957-4484/18/17/175101
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles as bimodal tools in magnetically induced labelling and magnetic heating of tumour cells: anin vitrostudy

Abstract: Localized magnetic heating treatments (hyperthermia, thermal ablation) using superparamagnetic iron oxide nanoparticles continue to be an active area of cancer research. The present study uses magnetic nanoparticles (MNP) as bimodal tools and combines magnetically induced cell labelling and magnetic heating. The main focus was to assess if a selective and higher MNP accumulation within tumour cells due to magnetic labelling (max. 56 and 83 mT) and consequently a larger heating effect occurs after exposure to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 40 publications
(59 reference statements)
1
55
0
3
Order By: Relevance
“…It is worth mentioning that Kettering et al previously employed ARA-MNPs for magnetic labeling and the heating of tumor cells. 20 The larger saturation magnetization M S (78 and 49 Am 2 / kg, for PLL-MNPs and ARA-MNPs, respectively) revealed that our homemade nanoparticles were consistent with the higher efficiency observed in the cell migration experiments, since the magnetic force exerted on a single cell is proportional to the magnetic moment of the incorporated MNPs for a given magnetic field value (and its spatial derivative).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…It is worth mentioning that Kettering et al previously employed ARA-MNPs for magnetic labeling and the heating of tumor cells. 20 The larger saturation magnetization M S (78 and 49 Am 2 / kg, for PLL-MNPs and ARA-MNPs, respectively) revealed that our homemade nanoparticles were consistent with the higher efficiency observed in the cell migration experiments, since the magnetic force exerted on a single cell is proportional to the magnetic moment of the incorporated MNPs for a given magnetic field value (and its spatial derivative).…”
Section: Resultssupporting
confidence: 81%
“…The commercial ARA-MNPs particles selected for this purpose were previously studied for labeling and heating purposes. 20 ARA-MNPs showed a larger hydrodynamic radius due to the presence of a polymeric matrix on the magnetic core and lower magnetic properties in terms of magnetization saturation and coercivity.…”
Section: Comparison Between Pll-coated and Commercial Fe 3 O 4 Mnpsmentioning
confidence: 99%
“…19 Although several publications reported that especially smaller MNP (approximately between 20 nm and 100 nm) were preferentially taken up by tumor cells (eg, by endocytosis), the possibility of the used MNP to be taken up by BT474 tumor cells or, at least, be bound to their membrane was verified in previous experiments. [20][21][22] Two hours after the application of thermoablative temperatures in the tumor region, a downregulation of BCL2 and FGF-R1 was found whereas HSP70 remained unchanged. Additionally, more apoptotic and necrotic areas were visible in close proximity to regions with high nanoparticle concentration in the treatment group (group 1) compared to the control group (group 2), indicating the eradication of tumor cells by using heat as a physical stressor.…”
Section: Discussionmentioning
confidence: 99%
“…We could show that magnetically based cellular MNP uptake by human adenocarcinoma cells is because of suitable magnetic field gradients that intensify the temperature increase generated during magnetic heating [20]. These strategies will provide new means to avoid the occurrence of regions of temperature underdosage during magnetic hyperthermia.…”
Section: The Intratumoral Temperature Pattern Might Well Be Influencementioning
confidence: 99%